Technical drawing with engineering graphics - Giesecke, Frederick E. (Frederick Ernest) 1869-1953; Hill, Ivan Leroy; Spencer, Henry C.; Dygdon, John Thomas; Novak, James E.; Lockhart, Shawna D.; Goodman, Marla (Pearson, 2014)
Technical Drawing and Engineering Graphics, Fourteenth Edition, provides a clear, comprehensive introduction and detailed, easy-to-use reference to creating 2D documentation drawings and engineering graphics by hand or using CAD. It offers excellent technical detail, up-to-date standards, motivating real-world examples, and clearly explained theory and technique in a colorful, highly visual, concisely written format. Designed as an efficient tool for busy, visually oriented learners, this edition expands on well-tested material, bringing its content up-to-date with the latest standards, materials, industries and production processes. Colored models and animations bring the material to life for the student on the book's companion website. Updated exercises that feature sheet metal and plastic parts are a part of the excellent Giesecke problem set.